Occupational Psychosocial Risks and Quality of Professional Life in Service Sector Workers with Sensory Processing Sensitivity - Antonio Chacón; María Luisa Avargues-Navarro; Manuela Pérez-Chacón; Mercedes Borda-Mas (Behavioral Sciences, 2023)
The aim of this study was to analyze the role of sensory processing sensitivity in the perception of stress under certain working conditions and its relationship with indicators of quality of professional life, in service sector workers. The participants (n = 3180) completed the Spanish versions of HSPS-S, CoPSoQ and ProQoL. The results show that exposure to certain working conditions represents a risk to the quality of professional life in workers of different fields, such as education, healthcare, hospitality and administration/management. The presence of high sensitivity is associated with poorer quality of professional life, specifically burnout and compassion fatigue. This study demonstrates the need to develop prevention programs aimed at managing stress by improving the working conditions, in order to adequately address sensory processing sensitivity and, consequently, promote the quality of professional life of service sector workers who present high sensitivity.